Bridging science communication and open science—Working inclusively toward the common good - Oliveira, Monique; Barata, Germana; Fleerackers, Alice; Alperin, Juan Pablo; Falade, Bankole; Bauer, Martin W. (Frontiers in Communication, 2024)
The 2020-2022 pandemic highlighted concerns about "information disorders", pressing for approaches capable of guiding the science-society alliance towards a mutually beneficial direction. This essay advocates for and presents a framework proposing the combination of Open Science (OS) and Science Communication (SciComm) practices. OS encourages public access to scientific material, while SciComm has historically enabled public understanding of scientific knowledge. Despite their similar goals, these two communities are disconnected. We draw on the concepts of "boundary object" and "epistemic trust" to demonstrate how this framework could foster a bond between scientific expertise and public reason towards an informed and inclusive common good. The OS-SciComm framework is based on the notion that ensuring transparency in science also requires "bridging tools" that deal with the complexity of scientific lexicon and processes. It values scientific expertise, but does not undermine citizens' capabilities in information processing and their interest in accessing scientific outputs. Our proposal also acknowledges controversies involving open scientific materials during the Covid-19 pandemic and advises caution when drawing conclusions from cases that are often context-specific. The OS-SciComm framework requires innovative ideas, platforms and actions. We invite both communities to join us in this endeavor.